Prevalence Of Diabetes Mellitus, Hypertension And Hyperlipidemia Among Students And Employees In University Of Tabuk, Saudi Arabia - Abdullah Altemani (European Scientific Journal, ESJ, 2016)
Background: Cardiovascular disease (CVD) is a common but chronic condition that can cause death, and is seen as a substantial source of disability and health costs. A balance between prevention and intervention, as is the case with other infectious diseases, is the best way to stem the increasing burden of CVD. Objective: This study assesses the prevalence of diabetes mellitus, hypertension, and hyperlipidemia in students and employees in a sample from the University of Tabuk. Methods: A crosssectional study was done in 2015, with 120 employees and students at the University of Tabuk (in Tabuk City, Saudi Arabia), for those over age 20 (60 males and 60 females) from different facilities and departments at the university. Findings: Blood testing was done with 120 participants to assess the prevalence of hypertension, diabetes mellitus, and hyperlipidemia at the University of Tabuk, in which the prevalence is actually higher than in most cities of Saudi Arabia. Ten percent of participants are hyperglycemic and 10% are developing problems in that area, with no significant difference between males and females. The overall percent of abnormal cholesterol levels is 17.5%. The mean total cholesterol level for female participants is significantly higher than that of males (160.1 vs. 157.3, p < 0.047). Conclusion: This information shows that cardiovascular risk factors will influence those with major health disorders in the future. Consequently, a nationwide campaign encouraging wholesome eating, better lifestyles, as well as physical activity, is a healthcare priority.